Effect of surface treatment on the dispersion of nano zirconia particles in non-aqueous suspensions for stereolithography. Issue 4 (April 2019) - Sun, Jinxing; Binner, Jon; Bai, Jiaming
Abstract: Stereolithography (SLA) requires the creation of stable and well dispersed ceramic suspensions with high solid loading in order to achieve dense ceramic parts. Five different dispersants used were stearic acid (SA), oleic acid (OA), Disperbyk (BYK), coupling agent KH560 and variquat CC 42 NS (CC). The results indicated that BYK, KH560 and OA are all capable of creating low viscosity, well dispersed suspensions with nanozirconia particles; of these 3 wt% BYK was the best option. 3 wt% BYK treated suspensions displayed shear thinning behaviour and had a viscosity of 1680 mPa s at a shear rate of 18.6 s −1 . A zirconia part was fabricated using the optimized suspension and its production followed the Beer-Lambert law. After sintering, a significant shrinkage was measured (21.9% in X–Y plane and 28.9% in Z directions), the SEM image showed the sintered part offered a high level of densification.